NON-CONTACT METHOD OF ESTIMATION OF STRESS-STRAIN STATE OF UNDERGROUND PIPELINES DURING TRANSPORTATION OF OIL AND GAS - Paweł DROŹDZIEL; Tetiana VITENKO; Liubomyr ZHOVTULIA; Andrii YAVORSKYI; Andrii OLIINYK; Ihor RYBITSKYI; Liubomyr POBEREZHNY; Pavlo POPOVYCH; Oksana SHEVCHUK; Vasyl POPOVYCH (Scientific Journal of Silesian University of Technology. Series Transport)
Development and implementation of contactless methods for determining the stress-strain state of pipelines in the process of transportation of energy hydrocarbons is important for ensuring its safe operation. The authors developed a method for determining the change in the stress-strain state of the underground part of the main oil and gas pipelines according to the data about the displacement of a certain set of points of the axis of the pipeline. This study was conducted on a linear section of the main gas pipeline, where a landslide in 2010 created a force pressure on the pipeline, resulting in a pipeline rupture.